Analisis Kesulitan Siswa Kelas VII Dalam Menyelesaikan Soal Penerapan Persamaan Linear Satu Variabel Di SMPN 4 Bukittinggi - Yudrikhul Khairat; Iltavia Iltavia; Yesminuryetti Yesminuryetti (Universitas Pahlawan Tuanku Tambusai, 2022)
The reason for this study is to find out the missteps made by students when dealing with the problem of applying one variable linear equations. Descriptive qualitative research is the research method used. The location of this research is SMPN 4 Bukittinggi. This study involved 27 students from class VII.G as subjects. The word test is provided as an instrument. According to the findings of this study, students had difficulty solving word problems because they did not understand the reading problem, which caused them to only write what was asked and what they knew. They also have difficulty making mathematical models, determining the results of the solution, using the wrong procedure, and writing the final answer. Because they are not familiar with algebraic calculation operations and have difficulty solving word problems, students have difficulty solving linear equation applications with one variable. Keywords: Student Difficulties, Application of PLSV